(untitled) (CAHIERS MAGELLANES-NS, 2024)
This study investigates the impact of technology adoption on small scale industries, focusing specifically on women entrepreneurs. Small scale industries play a crucial role in economic development, and their ability to adopt and integrate technology influences their competitiveness and sustainability. However, women entrepreneurs often face unique challenges in adopting technology due to social, economic, and cultural factors. This research aims to understand how technology adoption affects business performance, productivity, and market reach among women-led small-scale industries. The study employs a quantitative approach, surveying 110 women entrepreneurs to gather insights into their experiences, challenges, and outcomes related to technology adoption. Through a sample of 110 respondents, percentage analysis, rating analysis, correlation and ANOVA were employed. Results reveal significant the correlation coefficient between women entrepreneurship (WE) and Technology Adoption (TA) is 0.85, indicating a strong positive relationship between the two variables. Findings will contribute to the literature on small scale industries, women entrepreneurship, and technology adoption, providing valuable implications for policy makers, business support organizations, and women entrepreneurs themselves seeking to leverage technology for business growth and empowerment. The ANOVA analysis suggests that the challenges faced in adopting technology have a significant impact on business efficiency. The results indicate that addressing digital literacy and skills, and improving access to digital infrastructure, may have the greatest potential to improve business efficiency. Additionally, addressing high costs and cyber security concerns may also be important for improving business efficiency.